2020
DOI: 10.1161/hypertensionaha.119.14140
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Hypertensive Pregnancy Disorders and Mental Disorders in Children

Abstract: The associations of maternal hypertensive pregnancy disorders with offspring mental disorders remain unclear. We examined whether maternal hypertensive disorders and maximum blood pressure during pregnancy predict offspring childhood mental disorders, whether the associations are independent of maternal and paternal mental disorders and paternal hypertensive disorders, independent of or additive with maternal early pregnancy overweight/obesity and diabetes mellitus disorders, and mediated or moderated by prete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(81 citation statements)
references
References 35 publications
7
74
0
Order By: Relevance
“…Growth alteration, altered behaviors (anxiety, ADHD, cognition, depression) Rizzo et al, 1991;Sussman et al, 2013Sussman et al, , 2015von Geijer and Ekelund, 2015 Kattah and Garovic, 2013;Kleinewietfeld et al, 2013;Mao et al, 2013;Ha, 2014;Choe et al, 2015;Seravalli et al, 2016;Stocher et al, 2018;Afroz and Alviña, 2019;Faraco et al, 2019;Riise et al, 2019;Lahti-Pulkkinen et al, 2020 O 'Connor et al, 1988;Huang et al, 2001;Gambling et al, 2002Gambling et al, , 2004Lozoff and Georgieff, 2006;Alwan and Hamamy, 2015;Means, 2020 Zinc ↓ Preterm delivery, prolonged labor, hypertension, increased risk of infection Death, fetal malformations, growth delay, seizure, altered behaviors (anxiety, hypotonia, ADHD, social deficits) Donangelo and King, 2012;Roohani et al, 2013;Grabrucker et al, 2014Grabrucker et al, , 2016Sauer and Grabrucker, 2019 ↓, reduced; ↑, increased; ↑↓, imbalance; ↑↑↑, excessive; ASD, autism spectrum disorders; ADHD, attention-deficit-hyperactivity disorders; C-section, cesarean section; CNS, central nervous system; N/A, not available. Buyken et al, 2014;Castanon et al, 2015;Ludwig et al, 2018;Montalvo-Martínez et al, 2018).…”
Section: Specific Nutrient Imbalance and Inflammation Macronutrientsmentioning
confidence: 99%
“…Growth alteration, altered behaviors (anxiety, ADHD, cognition, depression) Rizzo et al, 1991;Sussman et al, 2013Sussman et al, , 2015von Geijer and Ekelund, 2015 Kattah and Garovic, 2013;Kleinewietfeld et al, 2013;Mao et al, 2013;Ha, 2014;Choe et al, 2015;Seravalli et al, 2016;Stocher et al, 2018;Afroz and Alviña, 2019;Faraco et al, 2019;Riise et al, 2019;Lahti-Pulkkinen et al, 2020 O 'Connor et al, 1988;Huang et al, 2001;Gambling et al, 2002Gambling et al, , 2004Lozoff and Georgieff, 2006;Alwan and Hamamy, 2015;Means, 2020 Zinc ↓ Preterm delivery, prolonged labor, hypertension, increased risk of infection Death, fetal malformations, growth delay, seizure, altered behaviors (anxiety, hypotonia, ADHD, social deficits) Donangelo and King, 2012;Roohani et al, 2013;Grabrucker et al, 2014Grabrucker et al, , 2016Sauer and Grabrucker, 2019 ↓, reduced; ↑, increased; ↑↓, imbalance; ↑↑↑, excessive; ASD, autism spectrum disorders; ADHD, attention-deficit-hyperactivity disorders; C-section, cesarean section; CNS, central nervous system; N/A, not available. Buyken et al, 2014;Castanon et al, 2015;Ludwig et al, 2018;Montalvo-Martínez et al, 2018).…”
Section: Specific Nutrient Imbalance and Inflammation Macronutrientsmentioning
confidence: 99%
“…Possible key confounding factors or moderators include familial confounding by maternal/parental mental health, other genetic or shared familial environmental influences, and maternal metabolic disorders during pregnancy (diabetes disorders and early pregnancy overweight/obesity). All these factors are highly comorbid with hypertensive pregnancy disorders [1,11,[27][28][29] and predict increased offspring risk of mental and behavioral disorders [30][31][32][33][34]. Furthermore, hypertensive pregnancy disorders increase the risk of preterm and SGA birth [5].…”
Section: Meta-analysesmentioning
confidence: 99%
“…Of the ten cohort studies [8][9][10][11][12][13][14][37][38][39], eight reported significant associations between maternal hypertensive pregnancy disorders and increased offspring risk of mental and behavioral disorders and two reported null findings. All cohort studies had many methodological strengths and received 5-9 stars in the NOS assessment (Table 2 and Supplementary Table 1 in the Online Data Supplement).…”
Section: Cohort Studiesmentioning
confidence: 99%
See 2 more Smart Citations